Developmentalism and the determinants of investment: an econometric exercise for Brazil in the 2000s - Feijo, Carmem; Braga, Julia de Medeiros; Corrêa, Mariana Finello (Brazilian Keynesian Review, 2019)
The aim of this paper is twofold. At first, we briefly review the current debate in Brazil between the new-developmentalists and the social-developmentalists. Both groups assume that the investment is the main component of aggregate demand to explain growth. However, the key variable to determine demand for investment is different for each group. For the new-developmentalists, the key variable is the real exchange rate. For the second group, public investment and domestic mass consumption are the most relevant variables. Given this debate, our next step is to test econometric models that capture the determinants of investment in Brazil in the 2000s. We start with the investment function presented by Bhaduri and Marglin (1990) and add other variables according to the developmentalist debate. We found robust results that confirm the validity of Bhaduri and Marglin´s hypothesis as well as the ones proposed by the new-developmentalists and the social-developmentalists.